Treatment adherence and support for people who inject drugs taking direct‐acting antiviral therapy for hepatitis C infection. Issue 11 (13th August 2019) - Read, Phillip; Gilliver, Rosie; Kearley, John; Lothian, Rebecca; Cunningham, Evan B.; Chronister, Karen J.; Dore, Gregory J.
Abstract: A community‐based public health facility in Sydney, Australia, the Kirketon Road Centre (KRC), provides health care to people who inject drugs (PWID), homeless and other marginalized people. Since March 2016, KRC has provided treatment for chronic hepatitis C virus (HCV) with direct‐acting antivirals (DAAs). We aimed to evaluate treatment adherence amongst clients taking DAAs in a highly marginalized population. All clients who commenced DAA therapy prior to March 2018 at KRC were included in this observational cohort with a subset of clients attending daily or weekly for enhanced adherence support and dosing. Demographic, behavioural, clinical measures and medication dosing were recorded, and adherence was calculated as the proportion of doses taken during the expected treatment duration. Factors associated with adherence were examined using logistic regression. A total of 242 individuals commenced DAA therapy, of whom 79 (32%) received enhanced adherence support. Enhanced support was associated with homelessness, daily injecting, Aboriginality, mental health co‐morbidity and poly‐drug use (all P  < .001). Overall adherence was 86%, and 92% of patients missed one or more doses (median 10, IQR 4‐24). At least 90% adherence during planned duration was seen in 38%, but increased to 66% by continuing therapy beyond planned duration. Intention‐to‐treat SVR12 was 68% and 66% in the enhanced adherence support sub‐population, with 29% lost to follow‐up by SVR12 testing. There were only 2 (0.8%) documented virological failures. Per‐protocol SVR12 was 99% and 96% in the enhanced adherence support sub‐population. In conclusion, adherence support may benefit those with multiple markers of marginalization. Extension of therapy beyond planned duration is a pragmatic strategy to enhance completion. Strategies to improve follow‐up, particularly post‐treatment are required.